THE EFFECT OF CORPORATE GOVERNANCE ON RETURN OF STOCK PRICE WITH COMPANY SIZE AS CONTROL VARIABLE - Wiryakusuma, I Gusti Bagus Yosia (International Business Management - Universitas Ciputra, 2019)
Good Corporate Governance (GCG) has a close relationship with public trust in a company. When a company implements GCG, it will provide security to shareholders. The safer shareholders feel, the more likely it will be for them to invest funds into the company sustainably. This should stabilize the company’s stock price. This study aims to examine the effect of GCG on stock price returns. In this study, secondary data was used, and linear regression was used to test the effect. The results of this study indicate that GCG has no effect on stock price returns.